PENGARUH PELATIHAN DAN KOMPETENSI TERHADAP PRESTASI KERJA KARYAWAN PADA PT TRIMITRA AGRO JAYA KOTA PEKANBARU - Muhammad Zul Padri; Resti Riandi; Desi Susanti (PT. Jurnal Center Indonesia Publisher, 2024)
The data analysis techniques used in this research are descriptive analysis techniques and inferential statistics which use the validity test formula, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t test, F test and coefficient of determination. The research results concluded that training partially influences work performance with a calculated t value of 5.085> t table 2.009 and a sig value of 0.000 < 0.05. Partially, competency has no effect on work performance with a calculated t value of 0.223 < t table 2.009 and a sig value of 0.824 > 0.05. Simultaneously training and competency influence performance. This can be seen from the F test results which show that the calculated F value is 27.522> F table 3.18 and the sig value is (0.000 <0.05). Then it was discovered that based on the coefficient of determination test, the adjusted R square value was 0.510 or 51%. This can be explained by the fact that the training and competency variables have 51% of the ability to explain the work performance variable and there is still 49% of the variance explained by other variables.